Evaluation of Efficacy and Safety of Low-Fluence Q-Switched 1064-nm Laser in Infra-orbital Hyperpigmentation Based on Biometric Parameters: Efficacy of Low-Fluence Q-Switched 1064-nm Laser in Infra-orbital Hyperpigmentation - Alavi, Shiva; Goodarzi , Azadeh; Nilforoushzadeh, Mohammad Ali; Mansouri, Parvin; Jafari, Mohammad Amin; Hejazi, Somayah; Azizian , Zahra (Journal of Lasers in Medical Sciences, 2022)
Introduction: Dark circles and wrinkles under the eyes are common cosmetic problems, caused by various conditions, especially aging and overproduction of melanin in the epidermis or dermis of the skin. In addition to the application of topical lightening agents, different types of lasers, especially the Q-Switched ND:YAG laser, has been used for the treatment of cutaneous hyperpigmentation. Because of a high prevalence of idiopathic eye dark circles (EDCs) or periorbital melanosis and a poor response to available therapies, we decided to evaluate the efficacy and safety of the Fractional QS 1064 nm ND:YAG Laser through a before-after trial. Methods: 18-65-year-old patients with skin Fitzpatrick phototype of I-V and without any usage of a topical or systemic therapeutic regimen (2-4 weeks before the trial) were enrolled in the study. Each patient was treated with 6 sessions of the Fractional QS 1064 nm ND:YAG Laser at 2-week intervals and assessed for response and possible side effects or recurrences through 4 outcome measures, including Visoface-based color and erythema, melanin index and lightness (Before the fourth and sixth sessions of the therapy; also 1 week and 3 months after finishing the trial). Results: The changes in Visoface-based color and erythema, the melanin pigment amount by the Mexameter (melanin index) and the degree of lightness by the Colorimeter of patients after 6 months of intervention were statistically significant (P<0.001). Conclusion: The fractional QS 1,064 nm ND: YAG Laser is an effective and safe therapy in EDCs since objective outcomes like the reduction of the melanin index and improving lightness and subjective ones like the reduction of darkness and erythema were confirmed. Doi:10.34172/jlms.2022.16.